(3OjhGf GHf GdJYGhjPis - (3GHf GdJYGhjPj , CHh GdaJM eMeO Hf YHjOGddg Hf YHO Gddg, GHf GdJYGhjPj,J (B583 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf GdJYGhjPi (B: (3CeG HYO MeO Gddg JYGdi eYeg GdSGHbI hChd eG ajg ef GdTYQ ef bUjOI jeOM HgG CejQ GdeDefjf s
(3BNQgG (B:s
(3MJi JQGgG dfG YbGdkG ai GdjO hGdQLd hGddSGf Je GdaUd GdQGHY ef GdRjGOGJ YfO fSNI hfbdg Edi ehVYgG GdPi jdjb HgG ef GdaUd hGdJLGhR Hefg haVdg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B278s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs